Community Satisfaction Index for the Posyandu Servant Program in Dusun Vii, Sukamaju Village, Percut Sei Tuan District, Deli Serdang Regency - Zuhrina Aidha; Mardiana Lestari Siahaan; Sri Bulan suci Ritonga; Deza Fernanda; Nelly Revita Lubis; Nasya Cantik Chairani; Zhafira Kurnia Anwar; Aulia Zahara; Anju Minta Marito; Siti Aziza Simatupang; Sabila Tamimi Siregar; Yuliawati Anggraini Siregar (Universitas Widya Gama Mahakam Samarinda, 2023)
Posyandu is a form of Community-Based Health Efforts (UKBM) whose role is indispensable for the community as the frontline in providing health services, especially for mothers, babies and toddlers. This study aims to determine the index of community satisfaction with posyandu services in Hamlet VII, Sukamaju Village. The research method used is approach qualitative research to examine the index of respondents’ satisfaction with the posyandu program. Data collection technique used is the interview technique and some related data and documents. The results of this study indicate that the people in Dusun VII Sukamaju Village show satisfaction with posyandu services due to the ease of requirements in obtaining services and the ease of obtaining information related to posyandu. Key words: Posyandu, Satisfaction Index, Health Service